Hamstring strains in high speed movements - Implications for injury prevention - Cronin, N. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Hamstring strain injuries (HSIs) are very common in sport, and the biceps femoris (BF) is the most frequently injured muscle. Activities involving large and/or fast hamstring strains present the greatest injury risk, e.g. soccer and sprinting. Importantly, the mechanism of HSI is poorly understood because hamstring length changes have not been directly studied in movements such as running, where injuries often occur. Thus, it is important to establish whether hamstring muscle fibres actually undergo lengthening during fast movements, and to assess whether these length changes are a possible source of HSIs. In theory, hamstring length changes can be studied with ultrasound imaging. However, this approach has severe limitations in fast movements, and where muscle deformations are substantial and occur in three dimensions. In this talk I will introduce our attempts to quantify BF strains in different tasks, and highlight the limitations of this method. I will also present multi-channel electromyography data showing how muscle activity varies along the length of hamstring muscles in different tasks. Finally, the relevance of these findings for injury mechanics and prevention will be discussed.